Pengaruh Perkembangan Teknologi Terhadap Metode Mengajar Pendidik di SMK Negeri 1 Sipoholon - Masrany Banjarnahor; Juwita Sipahutar; Eldina Sarah Nababan; Tioliza Manalu; Apriando Lumban Tobing (CV Putra Publisher, 2024)
The influence of technological developments on educators' teaching methods. In today's digital era, technology has changed the educational landscape by influencing the way educators deliver material and interact with students. This article discusses various changes that have occurred in teaching methods, such as the use of learning software, dare platforms, and interactive learning tools. Apart from that, we will also discuss the positive and negative impacts of technology in the educational process as well as the challenges faced by educators in integrating technology into the curriculum. Through literature, this article will conclude how important education is to technological developments in order to improve the effectiveness and quality of teaching in the future. The method used is the interview method, which is a technique commonly used in qualitative research and also in various other professional contexts, such as in the employee recruitment process or investigations.